ChemInform Abstract: Tribromoisocyanuric Acid in Trifluoroacetic Acid: An Efficient System for Smooth Brominating of Moderately Deactivated Arenes. Issue 27 (13th June 2013) - de Almeida, Leonardo S.; de Mattos, Marcio C. S.; Esteves, Pierre M.
Abstract TFA as the medium avoids polybromination which is observed for the same reaction in concentrated sulfuric acid.